Breast cancer stem cell selectivity of synthetic nanomolar-active salinomycin analogs. Issue 1 (December 2016) - Huang, Xiaoli; Borgström, Björn; Kempengren, Sebastian; Persson, Lo; Hegardt, Cecilia; Strand, Daniel; Oredsson, Stina
Abstract Background Cancer stem cells (CSCs) have been invoked in resistance, recurrence and metastasis of cancer. Consequently, curative cancer treatments may be contingent on CSC selective approaches. Of particular interest in this respect is the ionophore salinomycin, a natural product shown to be 100-fold more active against CSCs than clinically used paclitaxel. We have previously reported that synthetic salinomycin derivatives display increased activity against breast cancer cell lines. Herein we specifically investigate the CSC selectivity of the most active member in each class of C20-O -acylated analogs as well as a C1-methyl ester analog incapable of charge-neutral metal ion transport. Methods JIMT-1 breast cancer cells were treated with three C20-O -acylated analogs, the C1-methyl ester of salinomycin, and salinomycin. The effects of treatment on the CSC-related CD44+ /CD24− and the aldehyde dehydrogenase positive (ALDH+ ) populations were determined using flow cytometry. The survival ability of CSCs after treatment was investigated with a colony formation assay under serum free conditions. The effect of the compounds on cell migration was evaluated using wound-healing and Boyden chamber assays. The expression of vimentin, related to mesenchymal traits and expression of E-cadherin and β-catenin, related to the epithelial traits, were investigated using immunofluorescence microscopy. Results Treatment with each of the three C20-acylated analogs efficiently decreased the putative CSC population as reflected by reduction of the CD44+ /CD24− and ALDH+ populations already at a 50 nM concentration. In addition, colony forming efficiency and cell migration were reduced, and the expression of the epithelial markers E-cadherin and β-catenin at the cell surface were increased. In contrast, salinomycin used at the same concentration did not significantly influence the CSC population and the C1-methyl ester was inactive even at a 20 μM concentration. Conclusions Synthetic structural analogs of salinomycin, previously shown to exhibit increased activity against cancer cells, also exhibited improved activity against CSCs across several assays even at nanomolar concentrations where salinomycin was found inactive. The methyl ester analog of salinomycin, incapable of charge-neutral metal ion transport, did not show activity in CSC assays, lending experimental support to ionophoric stress as the molecular initiating event for the CSC effects of salinomycin and related structures.